2018
DOI: 10.1103/physreva.98.022318
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-encoded linear cluster states with coherent Raman photons

Abstract: Entangled multi-qubit states are an essential resource for quantum information and computation. Solid-state emitters can mediate interactions between subsequently emitted photons via their spin, thus offering a route towards generating entangled multi-photon states. However, existing schemes typically rely on the excitation-relaxation of the emitter, resulting in single photons limited by the emitter's radiative lifetime, suffering from considerable practical limitations, for self-assembled quantum dots most n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 82 publications
(115 reference statements)
0
14
0
Order By: Relevance
“…Most proposals of photonic graph states are based on pulsed polarization qubits—two orthogonal polarizations of light (e.g., horizontal and vertical, right and left circularly polarized) are treated as the |0 and |1 states, with different pulses being treated as different qubits. However, frequency‐encoded cluster states have also been proposed …”
Section: Photonic Graph Statesmentioning
confidence: 99%
“…Most proposals of photonic graph states are based on pulsed polarization qubits—two orthogonal polarizations of light (e.g., horizontal and vertical, right and left circularly polarized) are treated as the |0 and |1 states, with different pulses being treated as different qubits. However, frequency‐encoded cluster states have also been proposed …”
Section: Photonic Graph Statesmentioning
confidence: 99%
“…Define p(θ) as the distribution of random phases (supported on [0, 2π)), which dictates the distribution of effective measurement operators. This distribution depends on the physical scenario: in the example of frequency-encoded cluster-state generation in the hole-spin system in [2], when the precession time is much shorter than the emission time, p(θ)≈1/(2π). In such a case, the coherences of the reconstructed state would be completely washed out by conventional QST techniques (not making use of the knowledge of the errors θ).…”
Section: Sparse and Binned Tomographymentioning
confidence: 99%
“…Assuming a similar setup is used for the Lim et al scheme [37], we arrive at a similar phase distribution. On the other hand, for the first four schemes, γ represents the decay rate of the emitter due to spontaneous emission, whereas for the Scerri et al scheme [2] (which makes use of photonscattering), 1/γ is the loosely-optimised time between Y-rotations during which the emitter probabilistically scatters a photon. For the Lindner and Rudolph scheme [1], μ was calculated using parameters which give an error rate of 0.2%, whereas for the Denning et al scheme [38], the mean was calculated based on values suggested for high Q-factor cavities.…”
Section: Appendix B Pseudocodesmentioning
confidence: 99%
See 2 more Smart Citations